The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.jacbts.2020.06.004
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 and Calcific Aortic Valve Stenosis

Abstract: Corresponding Author

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Together, these results pave the way for more research that will clarify the mechanisms by which PCSK9 promotes CAVD in addition to its effect on lipid levels. 29 Our study also showed that PCSK9 acted as a downstream effector of AVCAPIR to mediate its procalcific effects. However, no significant changes in metabolic parameters (including total cholesterol, LDL, and triglycerides) were observed in AVCAPIR/ApoE DKO mice compared with ApoE –/– mice, suggesting that the lipid-lowering effects of PCSK9 inhibition were not involved in AVCAPIR deletion-elicited alleviation of calcification in AVC.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Together, these results pave the way for more research that will clarify the mechanisms by which PCSK9 promotes CAVD in addition to its effect on lipid levels. 29 Our study also showed that PCSK9 acted as a downstream effector of AVCAPIR to mediate its procalcific effects. However, no significant changes in metabolic parameters (including total cholesterol, LDL, and triglycerides) were observed in AVCAPIR/ApoE DKO mice compared with ApoE –/– mice, suggesting that the lipid-lowering effects of PCSK9 inhibition were not involved in AVCAPIR deletion-elicited alleviation of calcification in AVC.…”
Section: Discussionsupporting
confidence: 60%
“…Together, these results pave the way for more research that will clarify the mechanisms by which PCSK9 promotes CAVD in addition to its effect on lipid levels. 29 Our study also showed that PCSK9 acted as a downstream effector of AVCAPIR to mediate its The PIWI-interacting RNA AVCAPIR disrupted FTO-dependent m 6 A demethylation of CD36 mRNA, thereby leading to an increase in the N 6methyladenosine of CD36 mRNA, which was then recognized by m 6 A reader IGF2BP1 (insulin-like growth factor 2 mRNA binding protein 1) and leads to increased CD36 mRNA stabilization and abundance. In turn, the upregulated CD36 stabilized and promoted the abundance of procalcific PCSK9, thereby contributing to CAVD progression.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Loss of function due to PCSK9 R46L mutation reduces the risk of CAVS. 22 A clinical trial showed that the use of PCSK9 inhibitors decreased the hazard of new or worsening aortic stenosis. 23 But PCSK9 inhibitors mainly reduce LDL-C but not Lp(a).…”
Section: Mechanismmentioning
confidence: 99%
“…Other pioneer evidence supports the upregulation of HIF-1α in normoxic conditions—mediating the calcification process in AVICs. The ubiquitin E2 ligase C (UBE2C) is a member of the Anaphase Promoting Complex/Cyclosome (APC/C), which has been reported to also bind pVHL [ 88 ]. UBE2C upregulates the endothelial–mesenchymal transition (EndMT) and endothelial AV inflammation via the stimulation of HIF-1α levels through further ubiquitination and degradation of its upstream modulator pVHL, and this was accompanied by the reduction in microRNA-483–3p (miR-483) in HAECs [ 58 ].…”
Section: The Complex Interplay Of Hypoxia Signaling Mitochondrial Dys...mentioning
confidence: 99%